1991
DOI: 10.1007/bf00401520
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinaemia in obesity is not accompanied by an increase in serum proinsulin/insulin ratio in groups of human subjects with and without glucose intolerance

Abstract: Summary. Serum proinsulin is disproportionately elevated compared to insulin in Type2 (non-insulin-dependent) diabetes mellitus. We studied the effect of obesity on serum proinsulin with varying degrees of glucose intolerance. Serum proinsulin and insulin were measured during a 75 g oral glucose tolerance test in 73 obese and 74 non-obese subjects with normal, borderline or diabetic-type glucose tolerance. Proinsulin was assayed by a direct radioimmunoassay using proinsulin-specific antiserum. Fasting serum pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Furthermore, the nutrient signal, glucagon-like peptide (GLP_1), has been shown to readily reverse leptin activation of KATP channels in pancreatic â_cells (Keiffer et al 1997). This feedback mechanism may also explain the resistance to leptin observed in obese individuals even under conditions of hyperleptinaemia, as after the oral glucose tolerance test the plasma concentrations of insulin are increased from a fasting level of around 40-90 pm to 700-1800 pm (Shiraishi et al 1991). Thus it is likely that the high circulating levels of insulin associated with obesity and NIDDM prevent leptin activation of KATP and subsequent inhibition of insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the nutrient signal, glucagon-like peptide (GLP_1), has been shown to readily reverse leptin activation of KATP channels in pancreatic â_cells (Keiffer et al 1997). This feedback mechanism may also explain the resistance to leptin observed in obese individuals even under conditions of hyperleptinaemia, as after the oral glucose tolerance test the plasma concentrations of insulin are increased from a fasting level of around 40-90 pm to 700-1800 pm (Shiraishi et al 1991). Thus it is likely that the high circulating levels of insulin associated with obesity and NIDDM prevent leptin activation of KATP and subsequent inhibition of insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Because insulin-resistant individuals often have hyperinsulinemia, it is not clear whether hyperproinsulinemia per se is a marker of b cell distress. Therefore, disproportionally increased serum concentrations of proinsulin relative to insulin may be a surrogate marker of the failing pancreas (4), a phenomenon which has been reported in subjects with impaired glucose tolerance (8,11,19). However, the response of the normal b cell to increased demand has been hypothesized to result in enhanced processing of proinsulin into insulin (4).…”
Section: Introductionmentioning
confidence: 99%
“…High serum levels of PLM could be related to an increased secretory demand placed on -cells, as it has recently been shown to occur after hemipancreatectomy (Seaquist et al 1996), in the presence of glucose intolerance (Shiraishi et al 1991), in cystic fibrosis (Hartling et al 1988), or after prolonged intravenous glucose administration (Davis et al 1993). Cross-sectional data in NIDDM have shown that increased PLM occurs after the onset of hyperglycemia (Birkeland et al 1994).…”
Section: Introductionmentioning
confidence: 99%